Implementasi Program RT-BERSIH (Rapi, Tertib, Bersih, Sehat, Indah, dan Harmonis) - Jesiska Willius; Milwan; Sudirah (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2022)
Rukun tetangga has a strategic role in the implementation of communal-based development to build and empower RT as a small system so that it becomes better and will have a good impact on a better system in villages and sub-districts. This study aims to examine and analyze the implementation of the RT-BERSIH (Neat, Orderly, Clean, Healthy, Beautiful, and Harmonious) program initiated by the local government in Malinau Regency as an innovative regional program. A qualitative approach is carried out so that researchers can observe in detail and in depth through a direct approach to the object being observed. In collecting data several techniques have been carried out including interviews, observations, and data studies for reports and documents related to research. Based on the research results, the implementation of the Clean RT program in Pelita Kanaan Village provides good benefits for the four priority development targets, namely as follows: For the people's economy, the Clean RT program can create and improve household and RT scale business activities with assistance in the form of business equipment, livestock assistance, and entrepreneurship training in the field of human resources, this program can increase capacity and quality of life through tutoring and school activities. The implementation of the program is still constrained by the lack of human resources, especially among the management and supporting agencies. To reduce these barriers, village governments and local institutions provide ongoing training and assistance to administrators.